Peran Dan Sikap Pengasuh Terhadap Anak Tunarungu-Wicara Di Kompleks Halimun Bhakti Luhur Malang - Klemensia Nini; Yustina Muinesu (Jurnal Pelayanan Pastoral, 2021)
The roles and attitudes of caregivers greatly affect the growth and development of both physical and psychological, especially for children with hearing impairments. The better the role and attitude of caregivers towards speech-impaired children, the better their growth and development. On the other hand, the weaker the role and attitude of caregivers towards speech-impaired children, the worse their growth and development will be. It is not enough for caregivers to only pay attention to their physical needs but also to pay attention to their psychological needs such as affection, attention, security, and others. The purpose of this study was to describe how the role and attitude of caregivers towards speech-impaired children in the Bhakti Luhur Halimun complex as well as the supporting and inhibiting factors of the role and attitude of caregivers when accompanying speech-impaired children. This research is qualitative descriptive research. Methods of data collection using interviews, observation, and documentation. The findings of this study are 1) An impatient attitude is shown by caregivers when accompanying speech-deaf children, 2) Caregivers are less skilled in communicating with speech-deaf children, 3) Caregivers display inappropriate attitudes such as silencing and ignoring speech-deaf children if there are any. conflict with him, 4) There is an attempt by the caregiver to be gentle with the speech-impaired child, 5). The attitude of some caregivers towards the speech-impaired child is pity that drives the caregiver to give excessive attention, 6). There are efforts from some caregivers to understand the child's character so that it can help direct the child, 7) Some caregivers try to learn the form of communication used by the child even though it is limited. 8) The role can be carried out well, but it is not accompanied by an adequate attitude a heart.